Signaling pathways and targeted therapeutic strategies for polycystic ovary syndrome - Wang, Kexin; Li, Yanhua (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among women of reproductive age. Although promising strides have been made in the field of PCOS over the past decades, the distinct etiologies of this syndrome are not fully elucidated. Prenatal factors, genetic variation, epigenetic mechanisms, unhealthy lifestyles, and environmental toxins all contribute to the development of this intricate and highly heterogeneous metabolic, endocrine, reproductive, and psychological disorder. Moreover, interactions between androgen excess, insulin resistance, disruption to the hypothalamic–pituitary–ovary (HPO) axis, and obesity only make for a more complex picture. In this review, we investigate and summarize the related molecular mechanisms underlying PCOS pathogenesis from the perspective of the level of signaling pathways, including PI3K/Akt, TGF-β/Smads, Wnt/β-catenin, and Hippo/YAP. Additionally, this review provides an overview of prospective therapies, such as exosome therapy, gene therapy, and drugs based on traditional Chinese medicine (TCM) and natural compounds. By targeting these aberrant pathways, these interventions primarily alleviate inflammation, insulin resistance, androgen excess, and ovarian fibrosis, which are typical symptoms of PCOS. Overall, we hope that this paper will pave the way for better understanding and management of PCOS in the future.